Improved residual fat malabsorption and growth in children with cystic fibrosis treated with a novel oral structured lipid supplement: A randomized controlled trial - Stallings, Virginia A.; Tindall, Alyssa M.; Mascarenhas, Maria R.; Maqbool, Asim; Schall, Joan I. (PloS one, 2020)
In the primary analysis of a 12-month double-blind randomized active placebo-controlled trial, treatment of children with cystic fibrosis (CF) and pancreatic insufficiency (PI) with a readily absorbable structured lipid (Encala™, Envara Health, Wayne, PA) was safe, well-tolerated and improved dietary fat absorption (stool coefficient of fat absorption [CFA]), growth, and plasma fatty acids (FA). To determine if the Encala™ treatment effect varied by severity of baseline fat malabsorption. Subjects (n = 66, 10.5±3.0 yrs, 39% female) with baseline CFA who completed a three-month treatment with Encala™ or a calorie and macronutrient-matched placebo were included in this subgroup analysis. Subjects were categorized by median baseline CFA: low CFA (<88%) and high CFA (≥88%). At baseline and 3-month evaluations, CFA (72-hour stool, weighed food record) and height (HAZ), weight (WAZ) and BMI (BMIZ) Z-scores were calculated. Fasting plasma fatty acid (FA) concentrations were also measured. Subjects in the low CFA subgroup had significantly improved CFA (+7.5±7.2%, mean 86.3±6.7, p = 0.002), and reduced stool fat loss (-5.7±7.2 g/24 hours) following three months of EncalaTM treatment. These subjects also had increased plasma linoleic acid (+20%), α-linolenic acid (+56%), and total FA (+20%) (p≤0.005 for all) concentrations and improvements in HAZ (0.06±0.08), WAZ (0.17±0.16), and BMIZ (0.20±0.25) (p≤0.002 for all). CFA and FA were unchanged with placebo in the low CFA group, with some WAZ increases (0.14±0.24, p = 0.02). High CFA subjects (both placebo and Encala™ groups) had improvements in WAZ and some FA. Subjects with CF, PI and more severe fat malabsorption experienced greater improvements in CFA, FA and growth after three months of Encala™ treatment. Encala™ was safe, well-tolerated and efficacious in patients with CF and PI with residual fat malabsorption and improved dietary energy absorption, weight gain and FA status in this at-risk group.